(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aims to analyze the influence of destination image on destination loyalty with authenticity as a moderator in the Lon Malang Beach tourism, Sampang. The method used in this study is quantitative. The data collection technique used a questionnaire with a total of 97 respondents, and the respondents in this study were tourists who had visited Lon Malang Beach tourism, Sampang. The data analysis technique used is structural Equation modeling (SEM) with SmartPLS 4.1.1.5 software. The results of the study indicated that destination image has a significant effect on authenticity and destination loyalty. This finding underscores the importance of managing destination image and authenticity to strengthen destination loyalty and support sustainable tourism development.